Evaluating the Blade Leadership Development Program in Supporting PT Bukit Asam’s Business Transformation - Rumahorbo, Andrika Lestari; Febriansyah, Hary (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study evaluates the effectiveness of the Bukit Asam Leadership Acceleration and Development (BLADE) Program in supporting PT Bukit Asam’s (PTBA) strategic transformation agenda towards sustainable energy. Using the Kirkpatrick Evaluation Model (Levels 1–3) and Transfer of Training Theory, this qualitative case study explores how leadership competencies are learned and transferred into workplace behavior, as well as the alignment of the program with PTBA’s transformation target of generating 30% non-coal revenue by 2030. Data were collected through semi-structured interviews with alumni, program organizers, and top management, supported by secondary data such as annual reports and program documentation. Findings indicate that the program successfully enhanced participants’ leadership, interpersonal, and business management skills. However, transfer of learning varied across divisions, influenced by work environment and organizational support. While BLADE is aligned with PTBA’s long-term strategy, the absence of a structured post-program monitoring system limits its sustainable impact. The study highlights the importance of post-training interventions and organizational alignment to maximize leadership development outcomes in state-owned enterprises.